GCT-69. VOLUMETRIC CHANGE BEFORE CHEMORADIOTHERAPY AND INFLUENCE OF DIAGNOSTIC RADIATION EXPOSURE IN INTRACRANIAL GERMINOMAS. (4th December 2020) - Kagawa, Naoki; Hirayama, Ryuichi; Yokota, Chisato; Chiba, Yasuyoshi; Fujimoto, Yasunori; Nakagawa, Tomoyoshi; Umehara, Toru; Kijima, Noriyuki; Kinoshita, Manabu; Kishima, Haruhiko
Abstract: BACKGROUND: Spontaneous regression in intracranial germ cell tumors has been reported in some literatures, but the mechanism has not been well known. We retrospectively measured the tumor volume before chemoradiotherapy and analyzed factors that influence reduction of tumor volume. PATIENTS AND METHODS: Plural MRI scans were done before the first course of chemotherapy regimen in 27 patients with primary intracranial germinomas. Their age ranged from 8 to 31 years. 35 lesions from them were enrolled and included 13 pineal, 4 neurohypophyseal, 4 basal ganglia, 4 bifocal type, and 2 multiple lesions. All regions were verified as pure germinoma or HCG-producing germinoma by histopathological examination. Tumor volume of 35 lesions was analyzed by volumetric assessment based on MRI. Ratio of volumetric change between the first MRI and the scan immediately before chemotherapy was defined as shrinking rate (%). Period between disease onset and the first chemotherapy was 20 to 47 days. Diagnostic radiation dose was calculated in each case. RESULTS: Initial tumor volume ranged from 0.962 to 72.356 cubic centimeters (mean: 8.27). Diagnostic radiation dose: 40.5 to 910.1 mGy. Shrinking rate ranged from -57.8 to 85.4% (mean: 30.8). In 10 regions, shrinking rate was within 30%. Shrinking rate was significant positively influenced by diagnostic radiation dose (p<0.05) and negatively influenced by initial volume (p<0.05). But, other factors such as age, sex, histopathological parameters did not influence tumor shrinkage. CONCLUSION: This study shows that the volume of intracranial germ cell tumors is changing dynamically before chemoradiotherapy in many cases. Diagnostic exposure to low-dose radiation influences tumor shrinkage of intracranial germinomas.